MEDICAL WASTE MANAGEMENT AND MINIMIZATION EFFORTS AT PUBLIC HOSPITAL. CASE STUDY: PUBLIC HOSPITAL IN EAST JAKARTA, INDONESIA - Wulandari, Puri; Kusnoputranto, Haryoto (Universitas Ahmad Dahlan, 2015)
Medical waste is classified as hazardous waste and toxic materials. Equipped with various health facilities and visited by 1,267 people/day and occupancy rate is 68 percent in 2011, Public Hospital in East Jakarta generates a large number of medical wastes. Although medical waste generated less than domestic waste but potentially major cause of occupational accidents and illnesses transmission if not managed properly. This research aims to know how the hospital minimize and process the medical waste. Research methodology used in this research is qualitative approach from the aspect of the characteristics, effort minimization and management of medical waste. This research also used quantitative method by calculating the medical waste based on the occupancy rate and the service given. The results showed that the generation of medical waste as much as 0.9 pounds/ patient.days with 64 percent occupancy rate, while based on the type of service that is at most of the operating room of 0.67 pounds/ patient.days. Medical waste minimization efforts that have been done of segregation, housekeeping, preventive maintenance, clean technology, substitution of materials, and management of chemical and pharmaceutical, whereas only limited efforts to use waste reuse. The conclusion of this research was the minimization efforts do not do recycling and recovery, whereas the management of medical waste is not eligible especially separation, transport, storage, and management of ash from incineration of medical waste.